Some Aspects of Security Culture in Information Technologies - Stajić, Ljubomir; Radivojević, Nenad; Mirković, Vladan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Information technologies (IT), among other things, were created to preserve and improve human life and work in the field of communication, education, health preservation, environmental protection, etc. However, all technological innovations, in addition to positive ones, can have negative consequences for society itself (and its security). Thus, the development of IT is accompanied by numerous problems, questions and controversies that to a certain extent and in certain cases can lead to endangerment (individuals, groups, companies, states, the international community and humanity as a whole). This imposed the need to engage all (existing and new) social potentials in order to identify all the problems and consequences that the development and application of IT can leave for society. One of those potentials or mechanisms available to society is the security culture (in IT). Security culture is an absolutely positive category, and its basic function is tо prevent endangerment and to provide an optimal state of safety and security. In this regard, the subject of this work is the analysis of various aspects of security culture in IT (primarily ethical, sociological, economic and legal). The aim of the work is to expand the theoretical fund of knowledge in the field of security culture in IT, as well as to practically improve the actions and work of all those who participate in the creation (development) and application of IT.
Keywords: security, information technologies, security culture, security culture in information technologies, information security cultures.